Core fucosylation involvement in the paracrine regulation of proteinuria-induced renal interstitial fibrosis evaluated with the use of a microfluidic chip. (1st April 2022) - Liu, Anqi; Wang, Xiaolang; Hu, Xuemei; Deng, Yiyao; Wen, Xinyu; Lin, Bingcheng; Zhou, Mengying; Wang, Weidong; Luo, Yong; Deng, Jiu; Tang, Qingzhu; Du, Xiangning; et al.
Abstract: Proteinuria is a clinical manifestation of chronic kidney disease that aggravates renal interstitial fibrosis (RIF), in which injury of peritubular microvessels is an important event. However, the changes in peritubular microvessels induced by proteinuria and their molecular mechanisms remain unclear. Thus, we aimed to develop a co-culture microfluidic device that contains renal tubules and peritubular microvessels to create a proteinuria model. We found that protein overload in the renal tubule induced trans-differentiation and apoptosis of endothelial cells (ECs) and pericytes. Moreover, profiling of secreted proteins in this model revealed that a paracrine network between tubules and microvessels was activated in proteinuria-induced microvascular injury. Multiple cytokine receptors in this paracrine network were core-fucosylated. Inhibition of core fucosylation significantly reduced ligand-receptor binding ability and blocked downstream pathways, alleviating trans-differentiation and apoptosis of ECs and pericytes. Furthermore, the protective effect of genetic FUT8 deficiency on proteinuria overload-induced RIF and pericyte-myofibroblast trans-differentiation was validated in FUT8 knockout heterozygous mice. In conclusion, we constructed and used a multiple-unit integrated microfluidic device to uncover the mechanism of proteinuria-induced RIF. Furthermore, FUT8 may serve as a hub-like therapeutic target to alleviate peritubular microvascular injury in RIF. Statement of significance: In this study, we constructed a multiple-unit integrated renal tubule-vascular chip. We reproduced human proteinuria on the chip and found that multiple receptors were modified by FUT8-catalyzed core fucosylation (CF) involved in the cross-talk between renal tubules and peritubular microvessels in proteinuria-induced RIF, and inhibiting the FUT8 of receptors could block the tubule-microvessel paracrine network and reverse the damage of peritubular microvessels and renal interstitial fibrosis. This tubule-vascular chip may provide a prospective platform to facilitate future investigations into the mechanisms of kidney diseases, and target-FUT8 inhibition may be an innovative and potential therapeutic strategy for RIF induced by proteinuria. Graphical abstract: Image, graphical abstract